2022
DOI: 10.5194/egusphere-2022-1116
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Volyn biota (Ukraine) – 1.5 Ga old (micro)fossils in 3D-preservation, a spotlight on the ‘boring billion’

Abstract: Abstract. The Volyn biota, fossilized organisms with a minimum age of 1.5 Ga, were found in cavities in granitic pegmatites from the Korosten pluton, NW Ukrainian shield. Fossilization was due to influx of hydrothermal fluorine-rich waters, which silicified the outermost part of the organisms, thus preserving the 3D morphology. Details of the morphology (investigated by scanning electron microscopy) show that the majority of the specimens is filamentous, of a large variety with diameters ranging from ~10 µm to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…They were later reinterpreted as fossil cyanobacteria (Gorlenko et al, 2000;Zhmur, 2003) from a geyser-type deposit. Recent investigations (Franz et al, 2022(Franz et al, , 2023 have also identified a number of different fossils, some of them fungi-like. Filamentous fossils and remnants of former biofilms were also identified in etch pits of beryl.…”
Section: Morionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were later reinterpreted as fossil cyanobacteria (Gorlenko et al, 2000;Zhmur, 2003) from a geyser-type deposit. Recent investigations (Franz et al, 2022(Franz et al, , 2023 have also identified a number of different fossils, some of them fungi-like. Filamentous fossils and remnants of former biofilms were also identified in etch pits of beryl.…”
Section: Morionmentioning
confidence: 99%
“…The Alexander von Humboldt Foundation financially supported author V. Khomenko's stay in Berlin in 2022-2023…”
Section: Acknowledgmentsmentioning
confidence: 99%